Combining Ability and Genetic Parameters of Maize Based on S4 Diallel-Derived Progenies - Anggada Bima Satya Wibowo; Darmawan Saptadi; Budi Waluyo (Agro Bali : Agricultural Journal, 2026)
Maize is an important crop with strategic roles. The development of superior maize varieties requires genetically diverse parental lines with high combining ability. Advanced selfing generations, such as S4, provide increased homozygosity, allowing more reliable estimation of combining ability and genetic parameters for parental selection. This study aimed to evaluate general combining ability (GCA), specific combining ability (SCA), and genetic parameters using S4 progenies derived from a half-diallel mating design. The experiment was conducted from August to November 2025 at PT. Sukses Seed Sentosa, Malang Regency, East Java, Indonesia, using a randomized complete block design with two replications and involving 36 S4 cross combinations. The first two principal components of the GCA explained 82.36% of the total variation (PC1 = 63.26%; PC2 = 19.10%). P4 exhibited superior GCA for cob diameter and days to harvest, whereas P1 showed favorable GCA for multiple yield-related traits. SCA values showed that the first two principal components explained 84.54% of the total variation (PC1 = 74.46%; PC2 = 10.08%). P2 × P6 showed the highest SCA for multiple yield-related traits, while P2 × P4 was superior for days to silking and shelling percentage. High GCV was observed in AWC (25.26), SWC (25.62), and Y (23.79). High narrow-heritability was observed for DA (0.55), cob length (0.60), and NSPR (0.66). Most traits were predominantly controlled by additive gene action, whereas grain yield and number of seeds per cob were mainly governed by non-additive gene action.